The growth kinetics and in vitro biocompatibility of Nb2O5 microcones. (15th September 2010) - Mackey, A.; Karlinsey, R.L.; Chern, A.; Chu, T.G.
Metal oxides have been explored as potential surgical implant coatings designed to incorporate the biocompatibility of the surface oxide with the durable mechanical properties of the underlying metal. A novel anodisation process has been designed which generates an oxide composed of crystalline Nb2O5 microcones interspersed in an amorphous interface oxide. Thin sheets of niobium metal were anodised in a HF(aq) electrolyte for 1, 2 and 4 hrs. Scanning electron microscopy (SEM) was used to analyse the oxide features for each anodisation time. Larger and fewer microcones resulted from increased anodisation time. Due to the requirement of surgical implants to be autoclaved before implantation, the microcone features were analysed using SEM before and after autoclaving. Statistical analysis showed that the microcone features changed very little after autoclaving. MC3T3-E1 pre-osteoblast cells cultured on the autoclaved discs indicated that the 1 h and 4 h groups support the highest amount of cell proliferation.